Understanding the needs and challenges of a Black community in South Africa. Issue 3 (3rd April 2017) - McGhie, Venicia; Keim, Marion
ABSTRACT: This article reports on a study conducted with an unemployed group of community members residing in the Gugulethu Township in South Africa. The study aimed to gain an in-depth understanding of their needs and challenges, and what they thought could be done to assist and empower them so that they could improve their lives. Their basic human needs were violated during apartheid and as a consequence, they are still battling poverty today. We offer suggestions on how Black communities in South Africa could be supported and empowered in order to become employable and self-reliant.